2009
DOI: 10.1140/epjc/s10052-009-1042-y
|View full text |Cite
|
Sign up to set email alerts
|

Mass bounds on a very light neutralino

Abstract: Within the Minimal Supersymmetric Standard Model (MSSM) we systematically investigate the bounds on the mass of the lightest neutralino. We allow for nonuniversal gaugino masses and thus even consider massless neutralinos, while assuming in general that R-parity is conserved. Our main focus is on laboratory constraints. We consider collider data, precision observables, and also rare meson decays to very light neutralinos. We then discuss the astrophysical and cosmological implications. We find that a massless … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
161
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 259 publications
(431 reference statements)
12
161
0
Order By: Relevance
“…Notice that for M 2 = 200 GeV, values of µ ≃ 200 GeV are well within the allowed region independently of the value of tan β. The results in figure 2 are consistent with general analyses performed in the context of the MSSM [77].…”
Section: Jhep02(2013)001supporting
confidence: 88%
“…Notice that for M 2 = 200 GeV, values of µ ≃ 200 GeV are well within the allowed region independently of the value of tan β. The results in figure 2 are consistent with general analyses performed in the context of the MSSM [77].…”
Section: Jhep02(2013)001supporting
confidence: 88%
“…[95] for this model. Some general studies regarding light neutralinos can be found in [107][108][109][110][111][112][113][114][115][116]. On the other hand, in the regime of small Yukawa coupling f ∼ 10 −4 , the Higgs boson mass is devoid of any large tree level contribution.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
“…In this case, this is the lightest supersymmetric particle (LSP) and its mass is mainly controlled by the R-breaking Majorana gaugino mass parameter M 1 . A very light neutralino has profound consequences in both cosmology as well as in collider physics [107][108][109][110][111][112][113][114][115][116]. In the context of the present model one can easily satisfy the stringent constraint coming from the invisible decay width of the Z boson because the light neutralino is predominantly a bino.…”
Section: Jhep02(2015)124mentioning
confidence: 99%
See 1 more Smart Citation
“…Since χ 0 1 does not decay and does not interact with the detector, no direct limit can be obtained from this process. However the precise measurement of the Z-boson width imposes a limit of m χ 0 1 45 GeV, unless the neutralino has a very small (or zero coupling) to the Z, see e.g [28]. Searches for heavier charginos and neutralinos were essentially limited by the maximal LEP II center of mass energy of 209 GeV.…”
Section: Phenomenology and Limits On Electroweakinosmentioning
confidence: 99%